High Cytotoxic Efficiency of Lentivirally and Alpharetrovirally Engineered CD19-Specific Chimeric Antigen Receptor Natural Killer Cells Against Acute Lymphoblastic Leukemia - Müller, Stephan; Bexte, Tobias; Gebel, Veronika; Kalensee, Franziska; Stolzenberg, Eva; Hartmann, Jessica; Koehl, Ulrike; Schambach, Axel; Wels, Winfried S.; Modlich, Ute; Ullrich, Evelyn (Frontiers in Immunology, 2020)
Autologous chimeric antigen receptor-modified (CAR) T cells with specificity for CD19 showed potent antitumor efficacy in clinical trials against relapsed and refractory B-cell acute lymphoblastic leukemia (B-ALL). Contrary to T cells, natural killer (NK) cells kill their targets in a non-antigen-specific manner and do not carry the risk of inducing graft-versus-host disease (GvHD), allowing application of donor-derived cells in an allogenic setting. Hence, unlike autologous CAR-T cells, therapeutic CD19-CAR-NK cells can be generated as an off-the-shelf product from healthy donors. Nevertheless, genetic engineering of peripheral blood (PB) derived NK cells remains challenging and optimized protocols are needed. In our study, we aimed to optimize the generation of CD19-CAR-NK cells by retroviral transduction to improve the high antileukemic capacity of NK cells. We compared two different retroviral vector platforms, the lentiviral and alpharetroviral, both in combination with two different transduction enhancers (Retronectin and Vectofusin-1). We further explored different NK cell isolation techniques (NK cell enrichment and CD3/CD19 depletion) to identify the most efficacious methods for genetic engineering of NK cells. Our results demonstrated that transduction of NK cells with RD114-TR pseudotyped retroviral vectors, in combination with Vectofusin-1 was the most efficient method to generate CD19-CAR-NK cells. Retronectin was potent in enhancing lentiviral/VSV-G gene delivery to NK cells but not alpharetroviral/RD114-TR. Furthermore, the Vectofusin-based transduction of NK cells with CD19 CARs delivered by alpharetroviral/RD114-TR and lentiviral/RD114-TR vectors outperformed lentiviral/VSV-G vectors. The final generated CD19-CAR-NK cells displayed superior cytotoxic activity against CD19-expressing target cells when compared to non-transduced NK cells achieving up to 90% specific killing activity. In summary, our findings present the use of RD114-TR pseudotyped retroviral particles in combination with Vectofusin-1 as a successful strategy to genetically modify PB-derived NK cells to achieve highly cytotoxic CD19-CAR-NK cells at high yield.